Confined collapse of unbonded multi-layer pipe subjected to external pressure. (15th December 2016) - Bai, Yong; Yuan, Shuai; Cheng, Peng; Han, Peihua; Ruan, Weidong; Tang, Gao
Abstract: If a leakage exists on the outer sheath of an unbonded multi-layer pipe, external hydrostatic pressure will be applied on the surface of the internal sheath inducing the possibility of a confined collapse. Also, when the pipe bore is depressurized at a fast rate, the pressure remaining in the pipe wall can cause the similar collapse of the internal sheath. The present paper uses a flexible pipe with multi-layer structure to examine the mechanical response of the internal cylinder confined by outer cylinders under external pressure. The previous related researches mainly focus on the rigid or almost rigid confinement conditions. However, this study emphasizes on structural elastic stability in terms of the different confinement levels and D/t ratios of the internal cylinder. The initial investigation is numerical and employs two-dimensional models to obtain the nonlinear pressure-deformation equilibrium paths using a Riks algorithm. The results are fitted as uniform formulas for the prediction to the critical pressure and corresponding collapse modes. The simplified analytical model followed is developed through the principle of virtual work to compare with the fitting formulas. Experimental tests of an unbonded flexible pipe with simple construction are also conducted to validate and agree with the theoretical estimations.